2014
DOI: 10.2174/1389450115666141029234644
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Rituximab Therapy in Multiple Sclerosis: Review of Evidence Supporting the Need for Future Trials

Abstract: Rituximab has demonstrated a major effect in B-cell lymphoma and in a wide range of autoimmune disorders. Unfortunately, the blood-brain-barrier excludes the disorders restricted to the central nervous system (CNS) from the action of rituximab. The progressive phase of multiple sclerosis (MS) is a prototypical CNS autoimmune disorder characterized by an intrathecal compartmentalization of inflammation resisting all the available immunosuppressive treatments. As a consequence, intrathecal therapeutics are promi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 103 publications
0
16
0
Order By: Relevance
“…Third, given the presumable intrathecal compartmentalization of inflammation in the progressive stage, a potential drug needs to reach the CNS tissue in spite of a mostly intact BBB [25,106], e.g. by intrathecal application [107], or delivery into the CSF space via a shuttle system. Intrathecal application leads to locally maximized drug concentrations with low systemic exposure and can therefore be expected to have minimal systemic side effects [107].…”
Section: Requirements For Novel Ms Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, given the presumable intrathecal compartmentalization of inflammation in the progressive stage, a potential drug needs to reach the CNS tissue in spite of a mostly intact BBB [25,106], e.g. by intrathecal application [107], or delivery into the CSF space via a shuttle system. Intrathecal application leads to locally maximized drug concentrations with low systemic exposure and can therefore be expected to have minimal systemic side effects [107].…”
Section: Requirements For Novel Ms Therapiesmentioning
confidence: 99%
“…by intrathecal application [107], or delivery into the CSF space via a shuttle system. Intrathecal application leads to locally maximized drug concentrations with low systemic exposure and can therefore be expected to have minimal systemic side effects [107]. Fourth, besides immunomodulation and neuro-/myelin protection, the regenerative effects of treatments like anti-Nogo-A should foster repair as much as possible in this phase of disease.…”
Section: Requirements For Novel Ms Therapiesmentioning
confidence: 99%
“…Interestingly, GM haplotypes are in almost total linkage disequilibrium among world populations and are therefore typical of geographic origin unless there is a genetic admixture [60]. Gm21* haplotypes were associated with high ITS in a Caucasian population although Gm5*;3 haplotypes are associated with a low level of ITS 96,97 . Studies are required concerning non-Caucasian (African and Asian descent) haplotypes.…”
Section: Factors Influencing Its Levelmentioning
confidence: 99%
“…Given the low diffusion of rituximab to CSF (<0.2%) and the growing body of evidence demonstrating the safe use of intrathecally infused rituximab, a rationale to infuse intrathecal rituximab in progressive MS recently emerged (review in reference [96]). Data obtained from a single patient receiving intrathecal rituximab (10 mg per month for 2 months) showed a major effect upon CSF cytokine levels although intrathecal IgG synthesis was unchanged [97,98] (unpublished).…”
Section: None Of the Available Ms Drugs Deplete Intrathecal Ig Synthesismentioning
confidence: 99%
“…The results from preplanned subgroup analyses, however, suggested that it may affect disease progression in younger patients, particularly those with inflammatory lesions on brain MRI [14]. Given that the progressive phase of MS is thought to be associated with intrathecal compartmentalization of inflammatory cells, it has been suggested that intrathecal administration of immunosuppressants may represent a promising new approach in progressive MS [114]. A phase II trial of combined IV and intrathecally administered rituximab (vs placebo) in patients with SPMS is currently ongoing (NCT01212094).…”
Section: Rituximab and Ocrelizumab: 2 Anti-cd20 Monoclonal Antibodiesmentioning
confidence: 99%